Climate change and development in the Caribbean sub-region - Trotz, Ulric O'D. (2008)
Provides an overview of climate variability and change in the region. Looks at Greenhouse Gas emissions and mitigation and the impact of climate change. Focuses on adaptation options and management interventions. Concludes that the main obstacles to climate change adaptation in the sub-region are lack of awareness at the policy level, lack of capacity to develop decision support tools for policy makers, lack of resources and access to appropriate technology for adaptation on favourable terms.